KREATIVITAS GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI - Karimah, Akhlaqul; Shalahuddin, Rahmad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The purpose of this study is to describe the extent of PAI teacher creativity at SDN Sumbergedang II Pandaan, and also measure the learning interest of third-grade students at SDN Sumbergedang II Pandaan. This type of research uses a descriptive qualitative approach with field methods (field research). Data collection techniques were carried out by means of observation at SDN Sumbergedang II Pandaan, interviews with informants, namely teachers and third-grade students, and accompanied by documentation during research in the field. The results of this study describe that: teacher creativity in presenting PAI material is shown through the use of varied learning methods such as Lecture, Question and Answer, Group Work, Discussion, Travel, Role Play, etc. As for the condition of students' interest in learning PAI subjects at SDN Sumbergedang II Pandaan, which is quite a good learning interest, but out of 24 students there are 16 students who can overcome it, there are about 5 students who still do not understand how to overcome difficulties, and there are also 3 students who cannot at all how to overcome difficulties in the subject of Islamic religious education. There is also from the teacher's success in increasing students' interest in learning, regarding the success of students' interest in learning in Islamic religious education subjects, it can be concluded that there are 10 students who are very interested in increasing knowledge in Islamic religious education subjects, then there are 9 students who are interested (standard) in increasing knowledge in Islamic religious education subjects, and there are 5 students who are very interested in increasing knowledge in Islamic religious education subjects.